Design and evaluation of a phospholipase D based drug delivery strategy of novel phosphatidyl-prodrug. (July 2017) - Tao, Xinyi; Jia, Ning; Cheng, Nenghui; Ren, Yuhong; Cao, Xuni; Liu, Min; Wei, Dongzhi; Wang, Feng-Qing
Abstract: A strategy is proposed to design a safe and simple amphiphilic prodrug delivery system, based on the elevated expression of phospholipase D (PLD) in cancer cells. The method utilizes the transphosphatidylation ability of bacterial PLD on alcohol groups and the hydrolysis activity of overexpressed PLD on phospholipids in cancer cells. Doxorubicin (DOX) was selected as a test drug, and the phosphatidyl-doxorubicin (PX) was synthesized by bacterial PLD. The PX prodrug could be readily self-assembled to nanoparticles with uniform size and was stable during storage and circulation. The pharmacokinetics and biodistribution investigations indicated DOX could be selectively released from PX in cancer cells triggered by the local overexpressed PLD, and PX could significantly prolong the half-life of DOX in the tumors and decrease the distribution in heart and kidney. Moreover, the PX prodrug enhanced cellular uptake in MCF-7/ADR cells, demonstrating it could reverse the multi-drug resistance. Consequently, the prodrug displayed favorable anticancer efficacy in the MCF-7/ADR xenograft model without the cardiotoxicity and nephrotoxicity of DOX. The results demonstrated that phosphatidyl modification method can be used as an efficient strategy to develop a promising nanoscale drug delivery system for some drugs. Highlights: A novel strategy to develop self-assembled phosphatidyl prodrug catalyzed with PLD. Targeted drug release of phosphatidyl drug in tumor cells triggered by overexpressed PLD. High drug loading capacity and stability of phosphatidyl prodrug. Reduced toxicity and changed biodistribution resulted from the phosphatidyl modification of drug. Reversed effect of phosphatidyl prodrug on multidrug resistance cell.